(untitled) (Research, Society and Development, 2025)
For optimal building performance, it is essential to design foundation elements capable of effectively transmitting loads to the soil. In this context, a study is proposed to assess the feasibility of a shallow foundation resting on natural soil for a building located in João Pessoa, PB. The design of the shallow foundation was carried out, including verification of Ultimate Limit States (ULS) and Serviceability Limit States (SLS). Load-bearing capacity and immediate settlements were evaluated using the Schmertmann (1970) method, MEH, and the multilayer finite layer method. The results indicated that a shallow foundation on natural soil was unfeasible, leading to the consideration of shallow foundations combined with soil improvement techniques. Additionally, the possibility of implementing a deep foundation was examined as an alternative to soil improvement. A steel pile was selected based on the stratigraphic profile of the site, which includes soft clays and limestone rock at approximately 30 meters depth. The deep foundation design considered both the structural capacity of the steel profiles and the geotechnical bearing capacity, according to the Aoki and Velloso (1975) method. Based on the findings, a comparative cost analysis was conducted for the proposed methods, evaluating their technical and economic feasibility. It was concluded that the shallow foundation combined with soil improvement techniques offered the best cost-benefit ratio for the analyzed project.